Development of a multi-layered psychosocial care system for children in areas of political violence - Jordans, Mark JD (BioMed Central, 2010)
Few psychosocial and mental health care systems have been reported for children affected by political violence in low- and middle income settings and there is a paucity of research-supported recommendations. This paper describes a field tested multi-layered psychosocial care system for children (focus age between 8-14 years), aiming to translate common principles and guidelines into a comprehensive support package. This community-based approach includes different overlapping levels of interventions to address varying needs for support. These levels provide assessment and management of problems that range from the social-pedagogic domain to the psychosocial, the psychological and the psychiatric domains. Specific intervention methodologies and their rationale are described within the context of a four-country program (Burundi, Sri Lanka, Indonesia and Sudan). The paper aims to contribute to bridge the divide in the literature between guidelines, consensus & research and clinical practice in the field of psychosocial and mental health care in low- and middle-income countries.